STUDENT'S PERSPECTIVE ON THE IMPLEMENTATION OF SHORT DAILY CONVERSATION IN IMPROVING STUDENT'S SPEAKING ABILITY - Ayu Meiratnasari; Siti Yusilawati (Universitas Katolik Widya Mandala Surabaya, 2024)
The research aimed to explore students' perspectives on implementing Short Daily Conversation to improve students' speaking ability. The participants were 25 SMAN 1 Kretek Bantul students in Yogyakarta, Indonesia. The research was part of action research, which consisted of two cycles. The researcher conducted three interviews to collect the data. The first interview was before the implementation of Short Daily Conversation. The second interview was after cycle 1, and the last was after cycle 2. Moreover, the data was analyzed using a descriptive qualitative method. The research showed that the student's perception of implementing Short Daily Conversation to improve their speaking ability was positive. The students stated that implementing Short Daily Conversation in speaking class was interesting and could enhance their speaking ability.